Effects of ranibizumab (Lucentis®) and bevacizumab (Avastin®) on human corneal endothelial cells - Merz, Patrick; Ballikaya, Seda; Auffarth, Gerd U.; Schmack, Ingo (BMC ophthalmology, 2018)
Ingrowth of newly formed blood and lymph vessels (angiogenesis) from the limbus region into the cornea can be treated successfully by subconjunctival application of antiangiogenic agents. Currently, there are several angiogenesis inhibitors from various manufacturers available, such as vascular endothelial growth factor (VEGF) antibodies. The aim of the study was to investigate potential cytotoxic effects of two anti-VEGF agents, ranibizumab (Lucentis®) and bevacizumab (Avastin®) on the human corneal endothelium.
Gesehen am 21.12.2018